Evaluasi Program Latihan Kepemimpinan Organisasi Siswa Intra Sekolah di Pondok Pesantren Al-Hamid Putri - Mutia Nurul Alifa; Musringudin Musringudin (Jurnal Indonesia Sosial Sains, 2022)
Al-Hamid Putri Islamic Boarding School also carries out Basic Leadership Training activities to train students to organize, how to manage time, socialize, and express opinions. On the other hand, the formation of OSIS also plays a very important role in shaping the spirit of leadership. This study aims to evaluate the OSIS Leadership Training Program for the Al-Hamid Putri Islamic Boarding School. The research was conducted at the Al-Hamid Putri Islamic Boarding School, Cibubur. East Jakarta. The population and sample in this study were the participants of the OSIS Leadership Training Basic Al-Hamid Putri Islamic Boarding School. This research uses descriptive qualitative research method with KirkPatrick Evaluation Method. KirkPatrick's Evaluation Method focuses on 4 Levels of Evaluation Stages; Level 1 Reaction, Level 2 Learning Phase, Level 3 Behavior Phase, and Level 4 Outcome Phase. Level 1 Reactions provide positive satisfaction according to the participants' responses based on indicators of material, consumption, facilities and infrastructure and, presenters. Level 2 Learning Phase provides 80% response about understanding related to the material. Level 3 Behavioral Stage provides an 85% response related to significant changes related to the application of materials in daily life. Level 4 Stage Results obtained a response of 70% related to the increase in information and performance obtained after participating in the training. This training had a positive impact on changing the behavior of the participants at the Al-Hamid Putri Islamic Boarding School, Cibubur, East Jakarta.